Modular hybrid control for double-link two-wheeled mobile robot - Ahmad, Salmiah; Aminnuddin, Muthanna; M. Shukor, M. A. Sadiq (2012)
The use of Double-link inverted Pendulum (DIP) configuration for two-wheeled mobile robot has expanded the flexibility and function of the two-wheeled mobile robot. Although the second link introduced has increase the non-linearity and complexity of the system, yet a suitable control strategy can fully utilize its capability in being used as an extendable link, where it can reach higher level of height for pick and place task and can be located at any angle of interest provided the first link must be at balanced constantly. In this paper, a hybrid control consisting of fuzzy-PD type control and a conventional PID control were implemented hierarchically to control the angular position of both links. Simulation results show that the system performance really affected by the coefficient of proportional, integration, and differential of the PID controller and the scaling factors for fuzzy-PD for the first link. The good result has been obtained after several heuristic tuning stages of both controllers parameters and the system is able to maintain the upright position while the second link can be maintained at any angle.